Quantitative ultrasound (QUS) for the assessment of bone health. - Aqilah-SN SMZ; Zulfarina SM; Nazrun AS; Sabarul AM; Isa NM (Penerbit UKM, 2014)
Osteoporosis is known as a silent disease because bone density slowly decreases with advancing age and without symptoms. The incidence of osteoporosis is increasing yearly worldwide. Measuring bone mineral density (BMD) using conventional bone densitometry (DXA) is practical in diagnosis of osteoporosis but the cost is high and cannot be implemented in community. However, quantitativeultrasound (QUS) is a modern technique to measure the bone density and also for the diagnosis of osteoporosis. It is comparatively easy, reliable, less costly, and a safe method compared to other techniques. QUS consists of two main parameters which are known as broadband ultrasound attenuation (BUA) and speed of sound (SOS). QUS can also predict fracture risk of BMD. QUS showed significantly associated with BMD, bone micro architecture and mechanical parameters for In vitro studies and in human studies, QUS were found to be associated with BMD. Hence, QUS is capable to be new technique for bone assessment.